2020
DOI: 10.1177/1071181320641023
|View full text |Cite
|
Sign up to set email alerts
|

Team Synchronization and Individual Contributions in Coop-Space Fortress

Abstract: This work studied human teamwork with a concentration on the influence of team synchronization and in- dividual differences on performance. Human participants were paired to complete collaborative tasks in a simulated game environment, in which they were assigned roles with corresponding responsibilities. Cross- correlation analysis was employed to quantify the degree of team synchronization and time-lag between two teammates’ collective actions. Results showed that team performance is determined by factors at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In this paper, we proposed a novel adaptive agent framework in human agent teaming (HAT) based on the cross-entropy similarity measure and a pre-trained static policy library. The framework was inspired by human teamwork research, which illustrates important characteristics of teamwork such as the existence of complementary policies, influence of adaptive actions on team performance, and the dynamic human policies in cooperation [23], [24]. The CEM measure making it possible to directly measure and compare behavior among humans and agents provides a tool of broad applicability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we proposed a novel adaptive agent framework in human agent teaming (HAT) based on the cross-entropy similarity measure and a pre-trained static policy library. The framework was inspired by human teamwork research, which illustrates important characteristics of teamwork such as the existence of complementary policies, influence of adaptive actions on team performance, and the dynamic human policies in cooperation [23], [24]. The CEM measure making it possible to directly measure and compare behavior among humans and agents provides a tool of broad applicability.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing human teamwork also gives us a baseline when designing agents in terms of reward function and adaptive behaviors. The results of this human teamwork experiment are reported in more detail in [23], [24]. Here we briefly discuss the insights it brings to our work in human agent teaming.…”
Section: Human-human Teamsmentioning
confidence: 99%
“…In recent work, Li et al (2020) examined teammate collaboration and action adaptation during the mission in tightly coupled, time stressed teamwork. In collaborative tasks, the final outcome is determined by individual level (e.g., skill level, motivation, and personality) and team level (e.g., communication, team coherence, and complementary strategy) criterion of interest.…”
Section: Human Teammate Substitutementioning
confidence: 99%
“…Identifying teammate contributions is complicated by differences in play due to adaptation to other teammates leading to equilibria in which each player's actions and contributions may be quite distinct from team to team. In this work (Li et al, 2020), the researchers identified the components of team adaptation in more detail, with respect to not only the final outcome (performance measure) but also the adaptive behaviors that occur as the mission evolves, a quantification that is novel in the human factors and multi-agent literature. Space Fortress (Agarwal et al, 2019), a game that has been used extensively for psychological research, was adapted for investigate teams.…”
Section: Human Teammate Substitutementioning
confidence: 99%
“…Before constructing exemplar policies, we first evaluate the nature of this testbed through previous research in human-human teams. The results (Li et al 2020b) show that different human-human pairs demonstrate significantly diverse performance and the team performance was affected by both individual level factors such as skill levels and team level factors such as team synchronization and adaptation.…”
Section: Introductionmentioning
confidence: 98%